ANALYSIS OF FACTORS AFFECTING INVESTMENT DECISIONS WITH FINANCIAL TECHNOLOGY AS AN INTERVENING VARIABLE AMONG STUDENTS OF THE INSTITUTE OF BUSINESS AND TECHNOLOGY PELITA INDONESIA - Tang, Wilson; Chandra, Teddy; Panjaitan, Harry P. (Ridwan Institute, 2024)
The purpose of this study is to analyze the influence of financial literacy, self-efficacy and income on investment decisions, as well as whether Financial Technology is able to mediate the influence. The research contributes to the fields of financial behavior and investment decision-making by examining how Financial Literacy, Self-Efficacy, and Income impact students' investment decisions in an academic setting, with a particular focus on the mediating role of Financial Technology (Fintech). The data analysis technique used in this study was SEMPLS with the help of the SmartPLS application. The results of the test were as follows: (1) Financial literacy has a significant positive effect on the investment decisions of Pelita Indonesia students; (2) Self-efficiency had a positive and insignificant effect; and (3) Income had an insignificant positive effect; (4) Financial Technology mediates the effect of Financial literacy on the Investment Decisions of students; and (5) Financial Technology does not mediated the impact of Income on the decision of students. The findings could inform educational institutions and policymakers on how to improve financial literacy programs and support fintech adoption to foster better financial outcomes among students, potentially leading to more financially empowered and responsible young investors.